Implementasi Program Pengelolaan Penyakit Kronis (Prolanis) di Puskesmas Poasia Kota Kendari - Ulfayani Ramsar; Laksono Trisnantoro; Likke Prawidya Putri (Center for Health Policy and Management, 2017)
Background: The Chronic Disease Management Program (Prolanis) is a system of health services and proactive approach, implemented in an integrated manner involving participants, health facilities and BPJS Health in order to maintain health for BPJS Health participants who suffer from chronic diseases to achieve optimal quality of life With the cost of effective and efficient health services. Prolanis program is to improve the quality of life of BPJS participants who suffer from chronic diseases, especially diabetes mellitus (DM) type II and hypertension. This prolanis is implemented by a government-owned first-level health facility (FKTP). Aims: to describe the influence of external factors, internal and individual character to the scope of implementation of prolanis program in kendari city. Method: The research type is descriptive research with qualitative method by using single case study design. Informants in this study are stakeholders who play a role in the Implementation of Chronic Disease Management Program (Prolanis) at Poasia Health Center of Kendari City which consists of 12 informants. The way data collection is done is by observation, in-depth interviews, and document review. This research was conducted in April-May 2017. It was analyzed with qualitative abalisa. Result: From the result of the research, it is obtained from the external influences in this case the health service fully supports the prolanis activity. On the internal factors obtained puskesmas poasia is good enough to carry out prolanis. And on the character factor of the invidu still the lack of knowledge and understanding of the health personnel involved in the implementation of prolanis. Conclusion: improving the knowledge and understanding of health personnel involved in the prolanis program.